Reliability of intraoperative frozen section for the diagnosis of renal tumors suspicious for malignancy in children and adolescents. Issue 8 (18th January 2017) - Carrasco, Alonso; Caldwell, Brian T.; Cost, Carrye R.; Greffe, Brian S.; Garrington, Timothy P.; Bruny, Jennifer L.; Black, Jennifer O.; Cost, Nicholas G.
Abstract: Background: The ability of intraoperative frozen section (IFS) to reliably diagnose renal tumors in children and adolescents is largely unknown. The objective of our study is to evaluate the ability of IFS to establish a histologic diagnosis for renal tumors in this population. Methods: We reviewed our experience with patients who underwent IFS at the time of surgery for a renal tumor suspicious for malignancy from 2005 to 2015. The IFS was compared to the final pathology (FP). Data on concordance and reliability were analyzed. Results: One hundred thirty patients underwent surgical interventions for a renal tumor suspicious for malignancy, and 32 (25%) patients underwent IFS. Median turnaround time for IFS was 20 min (range 13–44). The histologic IFS diagnosis correlated with FP in 26 (81.2%) cases was discrepant in three (9.4%) cases, and IFS was deferred to FP in three (9.4%) cases (kappa 0.71, 95% confidence interval [CI]: 0.52–0.899, P < 0.001). The IFS correctly distinguished between Wilms tumor and non‐Wilms tumor in 30 (94%) cases (kappa 0.874, 95% CI: 0.705–1, P < 0.001). A total of 17 of 19 (89.5%) Wilms tumors were correctly diagnosed by IFS, yielding a sensitivity of 0.89 (95% CI: 0.67–0.99) and a specificity of 1 (95% CI: 0.75–1). Conclusion: IFS is a reliable tool to establish a histologic diagnosis and to differentiate between Wilms and non‐Wilms tumors in children and adolescents with renal tumors. The use of IFS should be encouraged in cases in which obtaining a diagnosis will provide guidance for important "real‐time" medical decision making, specifically additional adjunctive surgical procedures.